Recent advances in the understanding of molecular mechanisms of cartilage degeneration, synovitis and subchondral bone changes in osteoarthritis. (3rd July 2016) - Wei, Yingliang; Bai, Lunhao
ABSTRACT: Osteoarthritis (OA), the most common form of degenerative joint disease, is linked to high morbidity. It is predicted to be the single greatest cause of disability in the general population by 2030. The development of disease-modifying therapy for OA currently face great obstacle mainly because the onset and development of the disease involve complex molecular mechanisms. In this review, we will comprehensively summarize biological and pathological mechanisms of three key aspects: degeneration of articular cartilage, synovial immunopathogenesis, and changes in subchondral bone. For each tissue, we will focus on the molecular receptors, cytokines, peptidases, related cell, and signal pathways. Agents that specifically block mechanisms involved in synovial inflammation, degeneration of articular cartilage, and subchondral bone remodeling can potentially be exploited to produce targeted therapy for OA. Such new comprehensive agents will benefit affected patients and bring exciting new hope for the treatment of OA.